Keterkaitan Bank Tanah Dengan Tanah Terlantar Pasca Berlakunya Undang Undang Cipta Kerja - Indriasari, Evy; Pratama, Erwin Aditya (Universitas Pancasakti Tegal, 2022)
The purpose of this study is to examine the relationship between the Land Bank after the promulgation of the Job Creation Law and the existence of wasteland in Indonesia and what obstacles are found in the control of wasteland administration in Indonesia. Land has economic value and social value where there are often legal problems that arise because of it. Administrative recording of land rights is key in efforts to minimize potential legal problems that will arise in the future. This research method uses a type of literature research, the research approach uses a normative approach, data sources use secondary data, data are analyzed by qualitative methods. The results showed that the existence of the Land Bank accommodates the management of abandoned land in Indonesia, abandoned land is one of the potential assets of the Land Bank, therefore the close relationship between the Land Bank and abandoned land after the enactment of the Job Creation Law. That the Land Office launched the Trident program aims to find out valid and sustainable data, especially in the field of land. The Land Office program is aimed at administering the existence of wasteland and then the data is managed by the Land Bank.